The Reasons for a Divorce: Six Cases from the Religion Court of Purwokerto in Central Java, Indonesia - Irsyad, Syamsuhadi (SOSIOHUMANIKA, 2013)
ABSTRACT: Marriage is meant for good, but the fact is still found a marriage that is not able to achieve the noble goals as expected by the couple husband and wife; and mandated by the provisions of the Act No.1 of 1974 on the marriage of family a happy and everlasting. Sometimes the opposite is true, the family conflicts that can result in protracted divorce. In Article 1 of Law No.1 of 1974 on Marriage, it is determined âMarriage is a spiritual bond between a man with a woman, as husband and wife alone to form a happy and lasting family based on Godliness the Almightyâ. This research is a descriptive normative studies using qualitative case study method, which is intended to provide a clear and comprehensive overview of the divorce petition by the examination in a Court case, with reference to existing norms. Determination of the location of the research undertaken purposively in Purwokerto Religious Courts jurisdiction. The population in this study is the divorce cases filed with the Court of Religion Purwokerto during the year 2011. Things that underline the granting of the divorce petition is due to frequent quarrels and disputes because the wife is not obedient to her husband, less income for the necessities of life, the existence of an affair, left without saying goodbye, the husband of a persecution against the wife, and husband has done the secretly wedding unbeknownst to his wife.KEY WORD: Marriage, divorce, reasons of divorce, husband and wife, unhappy family, and Purwokerto Religious Courts jurisdiction.Â RESUME: Artikel ini berjudul âAlasan untuk Bercerai: Enam Kasus dari Pengadilan Agama Purwokerto di Jawa Tengah, Indonesiaâ. Perkawinan dimaksudkan untuk kebaikan, namun kenyataannya masih ditemui perkawinan yang tidak mampu mencapai tujuan yang mulia, sebagaimana diharapkan oleh pasangan suami isteri dan diamanatkan oleh ketentuan Undang-Undang No.1 Tahun 1974 tentang perkawinan, yaitu membentuk keluarga yang bahagia dan kekal. Kadangkala yang terjadi justru sebaliknya, konflik keluarga yang berkepanjangan dapat berakibat terjadinya perceraian. Dalam Pasal 1 UU No.1 Tahun 1974 tentang Perkawinan, ditentukan âPerkawinan adalah ikatan lahir-batin antara seorang pria dengan seorang wanita sebagai suami isteri untuk membentuk keluarga yang bahagia dan kekal berdasarkan Ketuhanan Yang Maha Esaâ. Penelitian ini merupakan penelitian normatif deskriptif dengan menggunakan metode studi kasus kualitatif, yang dimaksudkan untuk memberikan gambaran yang jelas dan menyeluruh mengenai alasan-alasan penyebab perceraian dalam pemeriksaan perkara di Pengadilan, dengan mengacu pada norma yang ada. Penentuan lokasi penelitian dilakukan secara purposif di wilayah hukum Pengadilan Agama Purwokerto. Populasi dalam penelitian ini adalah kasus perceraian yang diajukan ke Pengadilan Agama Purwokerto selama tahun 2011. Hal-hal yang mendasari dikabulkannya permohonan perceraian adalah dikarenakan sering terjadi pertengkaran dan perselisihan yang dikarenakan isteri tidak taat pada suami, nafkah untuk kebutuhan hidup kurang, adanya perselingkuhan, pergi tanpa pamit, suami melakukan penganiayaan terhadap isteri, dan suami melakukan pernikahan siri tanpa diketahui isteri. KATA KUNCI: Perkawinan, perceraian, alasan perceraian, suami dan isteri, keluarga tak bahagia, dan wilayah hukum Pengadilan Agama Purwokerto.About the Author: Dr. Syamsuhadi Irsyad is a Senior Lecturer at the Faculty of Law UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, Purwokerto, Central Java, Indonesia. He can be reached at: tukiranump@yahoo.comHow to cite this article? Irsyad, Syamsuhadi. (2013). âThe Reasons for a Divorce: Six Cases from the Religion Court of Purwokerto in Central Java, Indonesiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.6, No.1 [Mei], pp.49-56. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (March 12, 2013); Revised (April 17, 2013); and Published (May 20, 2013). Â  Â